Chilli-briquettes modify the temporal behaviour of elephants, but not their numbers - Pozo, R; Coulson, T; McCulloch, G; Stronza, A; Songhurst, A (Cambridge University Press, 2017)
Crop loss to foraging elephants is one of the most significant causes of conflict between people and elephants in areas where wild elephants share resources with people. Effective solutions to reduce the effects of human–elephant conflict on local livelihoods are thus essential to foster coexistence between elephants and people. We assessed the effectiveness of chilli-briquettes (bricks made of dry chilli, elephant dung and water) in altering elephants use of space in the eastern Okavango Panhandle, Botswana. We burned > 600 briquettes during the night over a 2-month period to test five treatments: frequent burning of (1) chilli and (2) chilli-free briquettes, occasional burning of (3) chilli and (4) chilli-free briquettes, and (5) a control treatment. Using camera traps and footprint surveys we assessed the number of elephants that used experimental sites, and the times at which they did so. We found elephants changed their movement behaviour from predominantly nocturnal to diurnal in areas where chilli-briquettes were burned throughout the night; however, there was no difference in the mean numbers of individuals between treatments with and without chillies. In other words, chilli-briquettes had a repellent but not a deterrent effect on elephants, keeping them away only at times when chilli-briquettes were smouldering. Based on these findings we recommend the use of chilli-briquettes as a method to deter elephants in the short term. In the long term, chilli-briquettes should be applied in combination with other larger-scale mitigation approaches, such as land management and cooperative community-based tools.